Stefan Swieżawski on the Role of the Common Sense (Sensus Communis) in Aquinas’s Epistemology - Przanowski, Mateusz (Roczniki Filozoficzne, 2025)
Although Thomas Aquinas regards the common sense (sensus communis) as possessing very important role within the process of sensual cognition, in his works he does not present a fully developed theory of the workings of sensus communis. Thus this concept is still a subject of lively discussion and the commentators propose various interpretations of the issue. Stefan Swieżawski also put forward his own take on sense communis, assuming that its most important task is “creation” of phantasms (phantasmata). However, this latter thesis is controversial, as nowhere in his writings does Aquinas indicate that sensus communis could be responsible for the emergence of phantasmata. Therefore, this paper offers an in-depth analysis of Aquinas’s understanding of sensus communis, on the basis of which the validity of Swieżawski’s proposal is assessed.